2015
DOI: 10.1007/s11999-014-4104-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Acetabular Orientation Varies Between Supine and Standing Radiographs: Implications for Treatment of Femoroacetabular Impingement

Abstract: Background Often, anteroposterior (AP) pelvic radiographs are performed with the patient positioned supine. However, this may not represent the functional position of the pelvis and the acetabulum, and so when assessing patients for conditions like femoroacetabular impingement (FAI), it is possible that standing radiographs better incorporate the dynamic influences of periarticular musculature and sagittal balance. However, this thesis remains largely untested. Questions/purposes The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…For example, the spatial orientation of the acetabulum may be affected by the position of the pelvis. Posterior tilt increases in standing position and the parameters that describe anterior and posterior acetabular coverage, which are important in describing pincer morphology, may change 50 53. Also, two orthogonal views of the femoral neck may not be sufficient to identify all instances of cam morphology 21.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the spatial orientation of the acetabulum may be affected by the position of the pelvis. Posterior tilt increases in standing position and the parameters that describe anterior and posterior acetabular coverage, which are important in describing pincer morphology, may change 50 53. Also, two orthogonal views of the femoral neck may not be sufficient to identify all instances of cam morphology 21.…”
Section: Discussionmentioning
confidence: 99%
“…With increased pelvis tilt causing increased pincer impingement findings being well known, the true functional tilt of a pelvis and how this affects pincer FAI is less known. More recently, in an attempt to study supine and standing changes, Ross et al [8] studied reformatted preoperative CT scans and compared them with standing AP radiographs. They measured percentage of anteversion, ischial spine signs, crossover sign, and posterior wall sign and showed only a significant difference in the amount of cranial and central anteversion measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of supine CT versus standing radiographs, Ross et al [8] found an increase in anteversion in the supine reconstructed CT scans; however, they were unable to show a difference in crossover sign, ischial spine sign, and posterior wall sign. They did not measure LCE angle or inclination [8]. A cadaveric laboratory study showed differences in LCE angle, inclination, and crossover sign with increasing pelvic tilt [4].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations